Technological leadership in industry 4.0 education: influence of digital transformation and ICT adoption - Abdallah, Asma Khaleel; Trifonov, Ivan; Samusenkov, Vadim (Institute of Advanced Engineering and Science, 2025)
The objective of this article is a systematic investigation into the effectiveness of information and communication technologies (ICT) usage within the framework of the educational model “industry 4.0”, focusing on the influence of digital transformation on technological leadership in educational institutions. The problem is insufficient technical equipment, uneven distribution of resources, and insufficient support for teachers. The solution lies in systematic innovative training and support for teachers, creating incentives to increase their motivation. The study employs an experimental research design, utilizing survey methods. The subjects of the research include six directors, six teachers, and 120 students from educational institutions in the United Arab Emirates (UAE) and the Russian Federation. According to the survey results, teachers have a positive attitude toward using ICT. A majority of teachers believe that the use of ICT has a positive impact on students’ academic achievements. Responses to open-ended questions indicate a lack or uneven distribution of technical equipment, emphasizing the need for training and support for teachers. One teacher suggesting the “introduction of incentives and rewards” raises the issue of creating a reward system for teachers, which could affect their motivation. Regarding students’ academic performance, the results show that students in educational institutions with active ICT integration demonstrate better results.